2010
DOI: 10.1017/s0022215110001891
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic otoscopy skills of community ear assistants in Western Nepal

Abstract: Introduction: Deafness is a major problem in developing countries. Rural communities tend to be affected more than urban ones, and chronic otitis media is common. The World Health Organization has proposed primary ear care as a method of providing otological services in developing countries. This study aimed to assess the diagnostic otoscopy skills of community ear assistants in rural Western Nepal.Materials and methods: Community ear assistants undertook the pre-operative evaluation of 92 patients selected fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 5 publications
0
13
0
1
Order By: Relevance
“…The initial search yielded 674 articles, which reduced to 420 after removal of duplicates (see online supplementary table 3). After screening of abstracts, 356 studies were excluded and after full-text review a further 30, leaving 38 studies that met the inclusion criteria 21 22 30–65. Further details are in the Preferred Reporting Items for Systematic Reviews and Meta-Analyses flow chart (figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The initial search yielded 674 articles, which reduced to 420 after removal of duplicates (see online supplementary table 3). After screening of abstracts, 356 studies were excluded and after full-text review a further 30, leaving 38 studies that met the inclusion criteria 21 22 30–65. Further details are in the Preferred Reporting Items for Systematic Reviews and Meta-Analyses flow chart (figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…The majority of studies have been published in the past decade (since 2008, n=30), with no relevant studies published before 1980. Studies took place in South Asia (n=13),30 36 43–45 48 55–59 61 65 Oceania (n=7),21 38 39 41 42 62 63 North America (n=7),22 35 37 47 49 50 60 South America (n=6)31–34 40 64 or Africa (n=5) 46 51–54…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In western Nepal, a programme for community ear assistants is very successful. 6 Workers receive intensive training in the diagnosis of ear diseases, and they are qualified to select patients for ear surgery. The present study showed that similar skills can also be obtained by specially trained nurses.…”
Section: Discussionmentioning
confidence: 99%